A superoxide dismutase/catalase mimetic nanomedicine for targeted therapy of inflammatory bowel disease. (October 2016) - Zhang, Qixiong; Tao, Hui; Lin, Yongyao; Hu, Ying; An, Huijie; Zhang, Dinglin; Feng, Shibin; Hu, Houyuan; Wang, Ruibing; Li, Xiaohui; Zhang, Jianxiang
Abstract: Oxidative stress, resulting from excessive generation of reactive oxygen species (ROS), plays a pivotal role in the initiation and progression of inflammatory bowel disease (IBD). To develop an efficacious and safe nanotherapy against IBD, we designed and developed a superoxide dismutase/catalase mimetic nanomedicine comprising a hydrogen peroxide-eliminating nanomatrix and a free radical scavenger Tempol (Tpl). To this end, an oxidation-responsive β-cyclodextrin material (OxbCD) was synthesized, and a Tpl-loaded OxbCD nanoparticle (Tpl/OxbCD NP) was produced. Hydrolysis of OxbCD NP could be triggered by hydrogen peroxide, leading to on-demand release of loaded Tpl molecules from Tpl/OxbCD NP. OxbCD NP was able to efficiently accumulate in the inflamed colon in mice, thereby dramatically reducing nonspecific distribution after oral delivery. In three mouse colitis models, oral administration of Tpl/OxbCD NP notably mitigated manifestations relevant to colitis, and significantly suppressed expression of proinflammatory mediators, with the efficacy superior over free Tpl or a control nanomedicine based on poly(lactide- co -glycolide) (PLGA). Accordingly, by scavenging multiple components of ROS, Tpl/OxbCD NP may effectively reduce ulcerative colitis in mice, and it can be intensively developed as a translational nanomedicine for the management of IBD and other inflammatory diseases.